Pedagogical strategies to develop oral expression skills - Saras Zapata, Édgar (2020)
The objective of this study was to determine the degree of influence of the application of pedagogical strategies on the level of oral expression in the students of the “Guamán Poma de Ayala” Application Campuses. On the basis of the systematization of the conceptual theoretical heritage, analysis, reflection and permanent contrast with the diagnosis data, I support the proposal of pedagogical strategies for the development of the capacity of oral expression. The type of research is experimental. The design is quasi-experimental (the information was collected through an input and output evaluation); the level is explanatory (the reason for the low level of oral expression and under what conditions it occurs was understood). Finally, important conclusions were drawn. The results are as follows: according to the entrance evaluation, regarding oral expression, the percentage of students who were at the beginning is 31% in the experimental group and 45% in the control group; those who were located in process, in the experimental group it was 44% and in the control group 48%. The students who showed outstanding achievement in the experimental group was 15% and in the control group 7%. According to the exit evaluation, 80% (24) of the experimental group showed outstanding achievement, and in the control group 20% (6). In process, 13% (3) of students from the experimental group were located; while in the control group the percentage is 57% (17). At the beginning, 7% (2) of students from the experimental group were located, unlike the control group, which amounts to 23% (6).